The Growth of Established Companies : A Study Case of the Car Body Industry in Ecuador, Addressed from a Financial Point of View - Morales Carrasco, Lilián Victoria (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2016)
This study addresses the internal factors of financial nature that are related to the financial behavior in the expansion strategy of companies. In order to address the problem of research, companies representing the car body industry were selected. A statistical correlation analysis was applied to three growth measurement scenarios; in each scenario, the dependent variables such as sales, utility and installed capacity were listed with financial indices that functioned as independent variables. The descriptive analysis identified two groups with respect to the time of incorporation of the companies: in one group the time of incorporation is from about 26 to about 49 years, for the oldest ones; while in the other group the youngest ones have less than 26 years of incorporation. The companies under study were established as micro and small companies, and reached a title of medium-sized enterprises, measured by the number of workers. The main results of the research show high correlations in three scenarios that indicate that the financial management, as an internal growth factor, is decisive when analyzing the growth of established SMEs in the automobile bodywork manufacture industry in the case of Tungurahua, Ecuador.